Fabrication and characterization of zinc oxide and lead zirconate titanate nanostructures / Ali Khorsand Zak - Zak, Ali Khorsand (2012)
Since 1990, research on nanostructures and nanoparticles has attracted the interest of many researchers. Several methods have been developed to fabricate nano-sized materials. The main concern is to establish method that can be used to produce these materials at low cost, which is attractive for industry. Based on this motivation, in this thesis, I attempt to develop and investigate new and modified routes for preparing ZnO and PZT nanostructures and nanoparticles, which are the two materials that have attracted the most interest in in this decade. The aim of this work is to design and modify simple, inexpensive, fast, and safe methods for preparing the nanopowders of these two materials on a large scale and to study the characteristics of the nanostructures, such as structure, morphology, and optical properties by various characterization tools. To date, four different preparation techniques have been used to prepare ZnO nanoparticles, i.e., sol-gel synthesis, sol-combustion synthesis, solvothermal synthesis, and sonochemical synthesis. In addition, the sol-gel synthesis process has been used to prepare PZT nanoparticles. Initially, ZnO nanoparticles were prepared by the sol-gel method in two different media, i.e., gelatin and starch. These two natural materials were used as the polymerization agent. ZnO NPs were also synthesized by the sol-combustion method in which DEA was used as the polymerization agent and stabilizer, and citric and nitric acids were used as fuel. In the second preparation technique, the ZnO nanoparticles and nanostructures were prepared by the solvothermal method. The ethanolamine family, (MEA, DEA, and TEA), was investigated to determine its effect on the morphology of the ZnO nanostructures. The ZnO nanostructures (rods and flowers) were prepared successfully using the third preparation technique, i.e., the sonochemichal method. NaOH and NH3 solutions were used to control the pH of the Zn2+. The sonication process was applied for 5, 15, 30, and 60 min. In the fifth preparation technique, the PZT nanoparticles were prepared by the modified sol-gel method. Polyethylenglycol (PEG) and 2-methoxyethanol (EGME) were used as separate solvents to prepare the PZT nanoparticles. The structures of the ZnO and PZT nanoparticles also were investigated theoretically. Different theoretical models, such as Williamson-Hall and the Size-Strain Plot, were applied to analyze the XRD data of the ZnO and PZT nanoparticles. We also investigated the effect of calcination temperature on the mechanical properties of the nanoparticles. In addition, we investigated the optical properties of PZT nanoparticles prepared in different solvents, i.e., PEG and EGME. The dielectric properties of the PZT nanoparticles (with and without PVDF matrix) were investigated in the frequency range of 100 Hz to 40 MHz. The characterization of the materials using various techniques, such as XRD, TEM, SEM, and UV-vis, proved that good quality (narrow size distribution and uniform morphology) ZnO nanoparticles can be produced by the preparation technique that uses gelatin, while good quality (narrow size distribution and uniform morphology) PZT nanoparticles can be produced by the preparation technique that uses 2-methoxyethanol. These preparation techniques are attractive because they can be used to prepare these nanoparticles in large-scale production facilities, which is suitable for industry. In the future, these preparation methods can also be modified to prepare other metal oxide nanostructures, such as MgO and NiO, which also have various potential applications, such as in the medical field and electronics industries.